2021
DOI: 10.1029/2020gc009368
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Textural and Chemical Evolution of Silica Fault Mirrors in the Wasatch Fault Damage Zone, Utah, USA

Abstract: Earthquake nucleation and propagation involves a dramatic reduction in dynamic fault strength (e.g., Scholz, 1998). Fault weakening mechanisms identified in natural rocks and deformation experiments include mineral decomposition and dehydration (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…has performed multiple analyses of tectonic lamellae and, notably, never observed amorphous silica associated with tectonic lamellae in quartz grains [40][41][42][43][44]. In addition, Houser et al [45] described finding tectonically-formed, nano-to micro-scale amorphous silica particles and nanofilms along active fault planes, but they reported no quartz grains with fractures containing amorphous silica. Multiple studies have observed amorphous silica within fractures, but only in impact-related shocked quartz and not in tectonic deformation lamellae [9,14,19].…”
Section: Key Analytical Studies Of Shock Fracturesmentioning
confidence: 99%
“…has performed multiple analyses of tectonic lamellae and, notably, never observed amorphous silica associated with tectonic lamellae in quartz grains [40][41][42][43][44]. In addition, Houser et al [45] described finding tectonically-formed, nano-to micro-scale amorphous silica particles and nanofilms along active fault planes, but they reported no quartz grains with fractures containing amorphous silica. Multiple studies have observed amorphous silica within fractures, but only in impact-related shocked quartz and not in tectonic deformation lamellae [9,14,19].…”
Section: Key Analytical Studies Of Shock Fracturesmentioning
confidence: 99%
“…The active trace of the WFZ is expressed within Quaternary sediments (Figure 1b), but a ∼300–400 m‐wide fault damage zone crops out within the footwall of the southern Brigham City segment. This damage zone hosts chlorite breccia and phyllonite, rare gouge, Fe‐oxide rich cataclasite a few to tens of millimeters in thickness, disseminated Fe‐oxide alteration, abundant ∼mm‐thick specular hematite (specularite) veins and FMs (Evans & Langrock, 1994), and silica‐rich FMs (Houser et al., 2021). Hematite FMs and veins are observed as principally distributed in the damage zones of mesoscale normal faults subsidiary to the trace of the active WFZ (McDermott et al., 2017).…”
Section: Wasatch Fault Zone and Hematite Fault Mirrorsmentioning
confidence: 99%
“…These high-gloss, light-reflective slip surfaces are composed of layered nano particles to micro particles that can form at seismic to subseismic slip rates (e.g., Siman-Tov et al, 2013;Verberne et al, 2013;Pozzi et al, 2018). Fault mirrors have been observed in a variety of rock types, including carbonate, siliciclastics, basalt, granite, hematite, and chert, and they occur at a variety of scales (square millimeter to greater than square meter surface area; Power and Tullis, 1989;Fondriest et al, 2013;Evans et al, 2014;Kuo et al, 2016;Borhara and Onasch, 2020;Houser et al, 2021). Some processes invoked for generating fault mirrors include thermal decomposition, melting, gel lubrication, frictional grinding and nanoparticle lubrication, crystal plastic deformation and recrystallization, and/or asperity flash heating (e.g., Collettini et al, 2013;Kirkpatrick et al, 2013;Smith et al, 2013;Pozzi et al, 2018;Ault et al, 2019;Han et al, 2011;De Paola et al, 2011).…”
Section: ■ Introductionmentioning
confidence: 99%